If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 3Z * 9 Reorder the terms for easier multiplication: 12 = 3 * 9Z Multiply 3 * 9 12 = 27Z Solving 12 = 27Z Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-27Z' to each side of the equation. 12 + -27Z = 27Z + -27Z Combine like terms: 27Z + -27Z = 0 12 + -27Z = 0 Add '-12' to each side of the equation. 12 + -12 + -27Z = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -27Z = 0 + -12 -27Z = 0 + -12 Combine like terms: 0 + -12 = -12 -27Z = -12 Divide each side by '-27'. Z = 0.4444444444 Simplifying Z = 0.4444444444
| x+4=-20+7x | | 6-2p=p+9 | | 91+17x-4x=-15 | | 20x^3+33x^2=7x | | 3x^2+4=6x | | 3(x+2)=6x+2 | | 9-7.5y+2y=5 | | 2(1.5(14)+3)=3.5(14)-1 | | -3.5x-19.5+9.8=10.74 | | 4x-1=6x+2 | | x-5=5x-49 | | 16(t-4)+5t=7(3t+3)-10 | | w/4+10=20 | | -7x+3-2x=21 | | 6x^3-8x=0 | | 5m^2+16m+15= | | 8m^2-42m+49=0 | | 17=3g+9-g | | 6x+7=y | | -7x+9-4x=-35 | | 9x^2+64x+7= | | -3.2w-2=4.5 | | 73=4x+5 | | 4(x-5)-2x=6 | | 6b+9=-4 | | 7+24f-25=7f | | 7208-220=0 | | -15=-7x-4x+7 | | 33r^2+82r-16= | | -0.05=-0.015x | | 8x+2=6x-10 | | 2b+4=8 |